The Instructional Leadership Strategies of School Principals to Enhance Teacher Professionalism: A Case Study of SDN Pasrepan I - Rimadani, Eprilia; Harris, Taufiq; Wahyudi, M. Furqon (The Future of Education Journal, 2026)
This study aims to analyze the instructional leadership strategies of school principals in enhancing teacher professionalism at SDN Pasrepan I. The background of this research is based on the ongoing challenges in improving teacher professionalism, particularly in adapting to curriculum changes, enhancing the quality of teaching, and fostering continuous professional development. This research uses a qualitative approach with a case study design. Data collection was carried out through in-depth interviews, classroom observations, and documentation studies involving the principal and teachers of SDN Pasrepan I. Data analysis was conducted using interactive analysis techniques, which include data reduction, data presentation, and drawing conclusions. The results of the study show that the school principal's instructional leadership strategies include formulating a clear learning vision, implementing continuous academic supervision, facilitating teacher professional development, and fostering a collaborative school culture. These strategies have proven to positively contribute to the improvement of pedagogical competence, commitment, and teacher professionalism. This study emphasizes the crucial role of the school principal's instructional leadership as a key factor in enhancing teacher professionalism in elementary schools.